The Data Acquisition System for the ATLAS Phase-II Tile Calorimeter Demonstrator - Argos Fernando Carrió (EDP Sciences, 2021)
The Tile Calorimeter (TileCal) is the central hadronic calorimeter of the ATLAS experiment at Large Hadron Collider (LHC). The TileCal readout system consists of about 10,000 channels. In 2025, the LHC will be upgraded leading into the High Luminosity LHC (HL-LHC). The HL-LHC will be capable to deliver an instantaneous luminosity up to seven times compared to the LHC nominal luminosity. The TileCal Phase-II upgrade will replace the majority of the on-detector and off-detector electronics using a new readout schema for the HL-LHC era. The on-detector electronics will digitize and transmit calorimeter signals to the off-detector electronics at the bunch crossing frequency. In the counting rooms, the off-detector electronics will store the digitized samples in pipelined buffers and compute reconstructed trigger objects for the first level of trigger. The TileCal Phase-II upgrade project has undertaken an extensive R&D program which includes the development of a Demonstrator module to evaluate the performance of the new clock and readout architecture for the HL-LHC. A Demonstrator module containing the upgrade on-detector readout electronics was built, tested during several test beam campaigns, and inserted into the ATLAS experiment. The Demonstrator module is operated and read out using a Tile PreProcessor (TilePPr) Demonstrator which enables backward compatibility with the present ATLAS Trigger and Data AcQuisition and the Timing, Trigger and Command systems. This contribution describes the components of the clock distribution and data acquisition system for the Demonstrator module, and its implementation in the ATLAS experiment.